2022
DOI: 10.1002/osp4.616
|View full text |Cite
|
Sign up to set email alerts
|

Internalized weight stigma in women with class III obesity: A randomized controlled trial of a virtual lifestyle modification intervention followed by a mindful self‐compassion intervention

Abstract: Background: Internalized weight stigma (Internalized-WS) is prevalent among individuals with severe obesity, particularly women, and is associated with shame, disordered eating, and weight gain. Effective, accessible interventions that address both severe (Class-III) obesity and Internalized-WS are needed. This randomized pilot trial evaluated the feasibility, acceptability, and preliminary efficacy of a fullyremote lifestyle modification intervention (LM) followed by mindful self-compassion training (MSC) or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 88 publications
0
3
0
Order By: Relevance
“… 15 Literature has found that experiences of stigma are more prevalent among those with class 3 obesity compared to those with lower BMIs. 37 , 38 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“… 15 Literature has found that experiences of stigma are more prevalent among those with class 3 obesity compared to those with lower BMIs. 37 , 38 …”
Section: Discussionmentioning
confidence: 99%
“…Inherent within weight‐stigma is the assumption that patients are to blame for having obesity, and that the reversal of obesity is a matter of personal responsibility 15 . Literature has found that experiences of stigma are more prevalent among those with class 3 obesity compared to those with lower BMIs 37,38 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation